A feminist companion to the Apocalypse of John - Levine, Amy-Jill; Robbins, Maria Mayo (Feminist companion to the New Testament and early Christian writings, 2009)
Gender and empire : sexualized violence in John's anti-imperial apocalypse / John W. Marshall -- 'They have not defiled themselves with women...' : Christian identity according to the book of Revelation / Hanna Stenström -- Women in myth and history : deconstructing John's characterizations / David L. Barr -- 'Teaching and beguiling my servants' : the letter to Thyatira (Rev. 2-18-29) / Pamela Thimmes -- Why can't the heavenly Miss Jerusalem just shut up? / Jorunn Økland -- Re-membering the whore : the fate of Babylon according to Revelation 17.16 / Caroline Vander Stichele -- Feminine symbolism in the book of Revelation / Adela Yarbro Collins -- Jezebel speaks : naming the goddesses in the book of Revelation / Mary Ann Beavis -- A man's choice : wealth imagery and the two cities of the book of Revelation / Greg Carey -- Unveiling the bride : Revelation 19.1-8 and Roman social discourse / Lynn R. Huber -- Hypermasculinity and divinity / Stephen D. Moore -- Ms.Calculating the endtimes : additions and conversation / Catherine Keller